Surgical Trends in the Treatment of Meniscal Tears: Analysis of Data From the American Board of Orthopaedic Surgery Certification Examination Database. (July 2016) - Parker, Benjamin R.; Hurwitz, Shepard; Spang, Jeffrey; Creighton, Robert; Kamath, Ganesh
Background: The indications and criteria for meniscal repair are expanding in parallel with new understanding in biomechanics, joint pathophysiology, and increased physician education. Purpose: To describe the practice patterns of arthroscopic meniscal treatment in recent years, compare the trends of arthroscopic meniscal repair versus arthroscopic meniscectomy, and compare sports fellowship–trained versus non–sports fellowship–trained surgeons in terms of arthroscopic meniscal treatment techniques among American Board of Orthopaedic Surgery (ABOS) candidates from 2004 to 2012. Study Design: Descriptive epidemiology study. Methods: The ABOS database was used to identify cases of meniscal repair, partial meniscectomy, and anterior cruciate ligament (ACL) reconstruction from 2004 to 2012. The number of surgeons contributing cases for each calendar year was also recorded, along with the number who had sports fellowship training. Rates were calculated as the number of procedures per surgeon per year. Trends were analyzed using Poisson regression analysis to model the rate of each procedure over time. Results: The rate of all meniscal procedures per surgeon decreased 12% from 18.4 cases per surgeon in 2004 to 16.2 cases per surgeon in 2012. There was a smaller decrease for sports fellowship–trained surgeons (7%) than for non–sports fellowship–trained surgeons (32%). The rate of meniscal repair cases per surgeon increased 37% from 1.6 to 2.2 cases per surgeon. The rate of meniscectomy cases decreased 17% from 16.8 to 14.0 cases per surgeon. When comparing fellowship-trained surgeons to non–fellowship-trained surgeons, there was no significant difference in meniscal repair rates over time. There was a decrease of 35% in rates of meniscectomy among non–fellowship-trained surgeons compared with 11% among fellowship-trained surgeons. Conclusion: This study provides insight into the current practice trends of recent orthopaedic training graduates in the treatment of meniscal tears. The results suggest that reported meniscal procedures have decreased overall among ABOS candidates but that meniscal repair cases have increased. The findings support the recent shift toward evidence-based medicine, with changing practice patterns that may reflect the dissemination of recent findings from large, high-quality research studies in this field.